Pitcairnia calcicola (Bromeliaceae), a New Species from the Tropical Dry Forest of Costa Rica - Grant, Jason; Morales, J. Francisco (My University, 1996)
Pitcairnia calcicola is described as a narrow endemic of the low limestone hills in the tropical dry forest of central Guanacaste Province, Costa Rica. It belongs to Pitcairnia subg. Pitcairnia, and appears to be most closely related to P. flagellaris L. B. Smith of Guatemala.